Industrial hemp in Colombia is the best alternative for a Green and Sustainable Economy - Garcia Zapata, Sergio Andres; Gómez Miranda, Oscar Mauricio; Parra Acosta, Yenny Katherine (Universidad Francisco de Paula Santander, 2025)
Industrial hemp is an alternative for Colombia's transition towards a green and sustainable economy. This study analyzes its economic, environmental and social impact, highlighting its potential to diversify agricultural production, reduce dependence on polluting raw materials and generate employment in rural communities. In economic terms, its integration in sectors such as the textile industry, construction and bioplastic strengthens the country's competitiveness and its positioning in international markets. Environmentally, its low water consumption, its carbon capture capacity and its contribution to soil regeneration make it a highly sustainable crop. At a social level, its production favors the inclusion of small producers, the substitution of illicit crops and rural development. Despite its advantages, the expansion of industrial hemp in Colombia faces regulatory and financial challenges that limit its adoption. Therefore, from a qualitative documentary review methodology, the need to strengthen public policies, facilitate access to financing and promote research and industrialization to maximize its impact is identified. The results of this study can contribute to the design of strategies that position hemp as a strategic sector within the Colombian bioeconomy, promoting more sustainable production models aligned with the country's environmental commitments.